2014
DOI: 10.1080/15685551.2014.971393
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel acrylate emulsion containing phosphorus and silicon prepared via semi-continuous seeded emulsion polymerization

Abstract: The novel acrylate emulsion containing phosphorus and silicon was prepared successfully via semi-continuous seeded emulsion polymerization. The conditions of synthesizing the novel emulsion were optimized. The films of the resultant emulsion were characterized by Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and contact angle (CA) determinator, respectively. Results show that the optimal condition synthesizing the novel emulsion was that the amount of PAM-200 is 2.00 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Therefore, it was necessary to control the usage amount of KH-570 to lower the cross-linking degree during the emulsion polymerization. In addition, Jiang et al (2015) compared the effects of different ways of adding KH-570 on the performance of the latex, and discovered that adding KH-570 after other monomers could reduce the time of KH-570 in the weak acid (phosphoric acid) emulsion. At the same time, the study had confirmed that a small amount of KH-570 could enhance the roughness, toughness and weather resistance of latex film (Lu et al , 2016; Sui et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was necessary to control the usage amount of KH-570 to lower the cross-linking degree during the emulsion polymerization. In addition, Jiang et al (2015) compared the effects of different ways of adding KH-570 on the performance of the latex, and discovered that adding KH-570 after other monomers could reduce the time of KH-570 in the weak acid (phosphoric acid) emulsion. At the same time, the study had confirmed that a small amount of KH-570 could enhance the roughness, toughness and weather resistance of latex film (Lu et al , 2016; Sui et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Silicon-containing polymers have many attractive surface properties, such as an exceptionally low glass transition (T g ) temperature, low elastic modulus, and good thermal and chemical stability. Organic silicon monomer with its coupling effect can effectively improve the adhesion of the polymer to a substrate [16]. In addition, the price of organic silicon monomer is lower than that of organic fluorine monomer, so the introduction of silicon monomer to polyacrylate latex can not only save costs but also improve adhesion performance.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, determining the relationship between particle coagulation and particle size distribution of final latex particles is still a matter of debate, for instance, Ishii et al [8] considered that a steady growth without the aggregation of particles was necessary for preparing monodisperse polymer particles; In contrast, Telford et al [9] considered that the monodisperse polymer particles could be obtained in the presence of particle coagulation.…”
Section: Introductionmentioning
confidence: 99%